Hypertrombicity - Castro Bianchino, Omar (Cirugía del Uruguay, 1971)
Thrombophilic states have their humoral expression in a triad: hyperadhesiveness and aggregability of plateletes; kinetic or chronometric hypercoagulability; dynamic or structural hypercoagulability. In surgery, these three pillars appear after the fifth day of the post-operatory period and decrease gradually after the 15th.